MI Science Concept Gen Z: Scientific Paradigm of the Transformative Era - Moch. Farich Alfani (STIT Attaqwa, 2025)
In the environmental sector of society in Indonesia, especially the scope of basic education, the impact of the transition era of the development revolution from generation x to the era of generation z revolution, the existence of these developments requires new challenges; ever-increasing needs, even the existence of the sovereignty of a teacher who increasingly must be galvanized. Unfortunately, not all teachers are in tune with the needs of education in the era of the 21st Century Industrial Revolution. So, it is still a polemic among academics lately. Among them; learning that still seems monotonous because of the background of awkwardness in the application of technology 4.0. In addition, the emergence of stagnation in developing between the combination of science and technology integrated with Islamic nuances, so it is not uncommon for Islamic elementary schools to only stop at the outfite standard of a less acceptable graduate profile, some even go out of business. Researchers used a systematic literature study using PRISMA (Preferred Reporting Items for Systematic Reviews and Meta Analyses). Data collection was carried out from research results that have been published in the period 2015 to 2023 in accredited national journals and reputable international journals. The results obtained from this research study include; 1) the concept of MI-an era-transformative paradigm, 2) the combination of integrating curriculum, models, and subjects.